Respiratory-gated auricular vagal afferent nerve stimulation (RAVANS) modulates brain response to stress in major depression. (October 2021) - Garcia, Ronald G.; Cohen, Justine E.; Stanford, Arielle D.; Gabriel, Aileen; Stowell, Jessica; Aizley, Harlyn; Barbieri, Riccardo; Gitlin, David; Napadow, Vitaly; Goldstein, Jill M.
Abstract: Background: Negative stress significantly impacts major depressive disorder (MDD), given the shared brain circuitry between the stress response and mood. Thus, interventions that target this circuitry will have an important impact on MDD. The aim of this study was to evaluate the acute effects of a novel respiratory-gated auricular vagal afferent nerve stimulation (RAVANS) technique in the modulation of brain activity and connectivity in women with MDD in response to negative stressful stimuli. Methods: Twenty premenopausal women with recurrent MDD in an active episode were included in a cross-over experimental study that included two functional MRI visits within one week, randomized to receive exhalatory- (e-RAVANS) or inhalatory-gated (i-RAVANS) at each visit. Subjects were exposed to a visual stress challenge that preceded and followed RAVANS. A Factorial analysis was used to evaluate the effects of RAVANS on brain activity and connectivity and changes in depressive and anxiety symptomatology post-stress. Results: Compared with i-RAVANS, e-RAVANS was significantly associated with increased activation of subgenual anterior cingulate, orbitofrontal and ventromedial prefrontal cortices and increased connectivity between hypothalamus and dorsolateral prefrontal cortex, and from nucleus tractus solitarii to locus coeruleus and ventromedial prefrontal cortex. Changes in brain activity and connectivity after e-RAVANS were significantly associated with a reduction in depressive and anxiety symptoms. Conclusions: Our study suggests exhalatory-gated RAVANS effectively modulates brain circuitries regulating response to negative stress and is associated with significant acute reduction of depressive and anxiety symptomatology in women with recurrent MDD. Findings suggest a potential non-pharmacologic intervention for acute relief of depressive symptomatology in MDD. Highlights: Exhalation-gated taVNS (e-RAVANS) upregulates brain response to negative stress. e-RAVANS has significant acute antidepressant and anxiolytic effects in MDD subjects. Respiration-gating may optimize taVNS therapeutic effects on major depression.